Diffusion Of Innovation in Digital Transformation of Kotakmedia Indonesia - Hanugrah Nur Muharrani Putri; Filosa Gita Sukmono (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2025)
This research analyzes the theory of diffusion of innovation in the digital transformation carried out by Kotakmedia Indonesia. With the rapid development of digital today, innovation is a demand for companies to survive. Diffusion of innovation is a concept that studies the spread of innovation in a social system. The case study method with a qualitative approach is used to emphasize the question of how the transformation process in depth at Kotakmedia Indonesia will be collected, interpreted and analyzed the results of the data. The results show that the digital transformation of Kotakmedia Indonesia is influenced by relative advantage, compatibility, and effective communication in the social system. the factors that form the innovation diffusion process at Kotakmedia Indonesia, which include knowledge of innovation and reinvention factors, external accountability factors, and organizational structure factors also play an important role in supporting the digital transformation carried out by the company. This transformation process has successfully increased branding, audience reach, and website traffic.